An Analysis of Benefit Flows in New Zealand Using a Social Accounting Framework - Omar Aziz; Nick Carroll; John Creedy (New Zealand Government, The Treasury, 2013)
This paper presents a social accounting model to examine the entrants, exits and transitions of individuals among a wide range of benefit categories in New Zealand. Transition rates and flows are estimated separately for periods before the global financial crisis (GFC) and periods following the crisis. The data were obtained from the Benefit Dynamics Dataset maintained by the Ministry of Social Development. The model is used to examine, using simulations, the implications for the time profile of changes in the stock of benefit recipients under a range of counterfactual situations. It is suggested that the model can provide a useful tool for policy analysis.
Keywords: I38; J11; 330; Social Accounting; Benefit Flows; Simulation; Sozialpolitik; Verteilungswirkung; Simulation; Sozialrechnungsmatrix; Neuseeland